Penerapan Food Plating Mahasiswa dalam Mengikuti Cooking Competition di Universitas Dian Nuswantoro - Khaeril Sungkawa; Ratna Puspita Dewi; Aditya Eka Widianto; Sholeh Madjid (Journal of Islamic Economics and Finance, 2024)
The presentation of food, including appetizers, soups, main courses and desserts, seems to continue to change according to developments over time or culinary arts discoveries made by culinary artists. Not only culinary experts have developed the art of arranging dishes, but tourism campuses or culinary academies also often hold cooking competitions to encourage creativity in how to arrange and present a dish on a plate, where the presentation must pay attention to the position and composition of the food to become an artistic value. attractive and high quality. The author is interested in researching the application of food plating in cooking competitions. This research uses a qualitative approach with analytical descriptive research. And uses observation methods, interview methods, and literature study methods. The research sample was taken from competition participants. Data collection was carried out by directly observing students' application of food plating in preparation for cooking competitions. The results of the research show (1) by applying food plating where the position and composition of the food is taken into account so that the dish has high quality artistic value. (2) Competitors are able to arrange a dish systematically by paying attention to the position and composition. (3) The competition participants succeeded in describing the position and composition of the food on the plate by combining Indonesian food arranged with western style food plating so that they won second place in the cooking competition.